The Influence of Profitability, Liquidity, Firm Size, Business Risk, Growth, and Asset Tangibility On Capital Structure - Naibaho, Donna E.; Kristanti, Farida Titik (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Capital structure can provide an overview of the company's financial ratio between its own capital and long-term debt. Capital structure is the ratio between debt and equity. This research aims to determine the influence of profitability, liquidity, firm size, business risk, growth and asset tangibility on the capital structure of basic industrial and chemical sector companies listed on the Indonesia Stock Exchange for the 2016-2023 period. The research method used is a quantitative method. The regression model used is dynamic panel data regression with the Generalized Method of Moment (GMM) estimator using Eviews 12 software. The research results show that profitability, firm size, business risk and asset tangibility partially have a significant positive and negative effect on capital structure. Meanwhile, the liquidity and growth variables partially have no effect on capital structure.